2021
DOI: 10.3389/fonc.2021.681905
|View full text |Cite
|
Sign up to set email alerts
|

Construction and Validation of a Serum Albumin-to-Alkaline Phosphatase Ratio-Based Nomogram for Predicting Pathological Complete Response in Breast Cancer

Abstract: BackgroundBreast cancer patients who achieve pathological complete response (pCR) after neoadjuvant chemotherapy (NAC) have favorable outcomes. Reliable predictors for pCR help to identify patients who will benefit most from NAC. The pretreatment serum albumin-to-alkaline phosphatase ratio (AAPR) has been shown to be a prognostic predictor in several malignancies, but its predictive value for pCR in breast cancer is still unknown. This study aims to investigate the predictive role of AAPR in breast cancer pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 51 publications
3
6
0
Order By: Relevance
“…concluded that BMI was not a predictive biomarker for pCR, which was similar to the result of our study ( 48 ). Furthermore, our study confirmed that tumor makers, axillary LN positive, menstrual status before NACT ( 49 ), and albumin levels ( 50 ) did not show significant values in predicting PCR, which was consistent with previous studies.…”
Section: Discussionsupporting
confidence: 92%
“…concluded that BMI was not a predictive biomarker for pCR, which was similar to the result of our study ( 48 ). Furthermore, our study confirmed that tumor makers, axillary LN positive, menstrual status before NACT ( 49 ), and albumin levels ( 50 ) did not show significant values in predicting PCR, which was consistent with previous studies.…”
Section: Discussionsupporting
confidence: 92%
“…Breast cancer (BC) is the most common female malignancy worldwide and is one of the leading causes of morbidity and mortality. [1][2][3] Metastases, especially bone metastases, play an important role. 4,5 With the continuous improvement of early diagnostic methods and comprehensive treatments, the survival of BC has significantly increased.…”
Section: Introductionmentioning
confidence: 99%
“…4 Alkaline phosphatase (ALP) is a nonspecific enzyme that hydrolyzes phosphate in alkaline medium and its total level reflects the combined activity of several isozymes found in the bone, liver, kidney, and intestinal lining. 1,7 Its bone-specific isoforms (bone-specific alkaline phosphatase, BAP) originates in osteoblasts that release large amounts of the enzyme when bone repair activity occurs, for example bone metastases. 8,9 In the last few decades, hundreds of studies have reported the clinical value of ALP/BAP in BC and a significant increase in serum ALP was observed, which had been demonstrated to predict bone and liver metastases.…”
Section: Introductionmentioning
confidence: 99%
“…A total of three studies 32 , 33 , 56 investigated the value of albumin in predicting a pCR in breast cancer. These three studies were included in the meta-analysis, with a total of 772 patients and 162 with a pCR.…”
Section: Resultsmentioning
confidence: 99%